Conserved motifs in the hypervariable domain of chikungunya virus nsP3 required for transmission by Aedes aegypti mosquitoes. - Giel P Göertz; Marit Lingemann; Corinne Geertsema; Marleen H C Abma-Henkens; Chantal B F Vogels; Constantianus J M Koenraadt; Monique M van Oers; Gorben P Pijlman (Public Library of Science (PLoS), 2018)
BACKGROUND:Chikungunya virus (CHIKV) is a re-emerging arthropod-borne (arbo)virus that causes chikungunya fever in humans and is predominantly transmitted by Aedes aegypti mosquitoes. The CHIKV replication machinery consists of four non-structural proteins (nsP1-4) that additionally require the presence of a number of host proteins for replication of the viral RNA. NsP3 is essential for CHIKV replication and has a conserved macro, central and C-terminal hypervariable domain (HVD). The HVD is intrinsically disordered and interacts with various host proteins via conserved short peptide motifs: A proline-rich (P-rich) motif that has affinity for SH3-domain containing proteins and duplicate FGDF motifs with affinity for G3BP and its mosquito homologue Rasputin. The importance of these motifs for infection of mammalian cells has previously been implicated. However, their role during CHIKV infection of mosquito cells and transmission by mosquitoes remains unclear. METHODOLOGY / PRINCIPAL FINDINGS:Here, we show that in-frame deletion of the P-rich motif is lethal for CHIKV replication in both mosquito and mammalian cells. However, while mutagenesis of the P-rich motif negatively affects replication both in mammalian and mosquito cells, it did not compromise the infection and transmission of CHIKV by Ae. aegypti mosquitoes. Mutagenesis of both FGDF motifs together completely inactivated CHIKV replication in both mammalian and mosquito cells. Importantly, mutation of a single FGDF motif attenuated CHIKV replication in mammalian cells, while replication in mosquito cells was similar to wild type. Surprisingly, CHIKV mutants containing only a single FGDF motif were efficiently transmitted by Ae. aegypti. CONCLUSIONS / SIGNIFICANCE:The P-rich motif in CHIKV nsP3 is dispensable for transmission by mosquitoes. A single FGDF motif is sufficient for infection and dissemination in mosquitoes, but duplicate FGDF motifs are required for the efficient infection from the mosquito saliva to a vertebrate host. These results contribute to understanding the dynamics of the alphavirus transmission cycle and may help the development of arboviral intervention strategies.